Rhizome oil of Curcuma ochrorhiza Val. - Mohd Sirat, Hasnah; Jamil, Shajarahtunnur; A. Rahman, Ahmad (Allured Publishing Corp., 1997)
The chemical composition of the rhizome oil of Curcuma ochrorhiza isolated by hydrodistillation was analyzed by capillary GC, GC/MS and 1H-NMR. The main constituents found in the oil were furanogermenone (53.14%), germacrone (9–62%) and β-elemene (8.84%, camphor (6.31%) and isofuranodiene (5.61%).